Effects of ball combination training program combined with cTBS intervention on motor disorder in children with autism spectrum disorder - Kai Qi; Zhiyuan Sun; Yifan Shi; Xuan Xiong; Yufei Liu; Kelong Cai; Aiguo Chen; Marcin Białas (Scientific Reports)
Abstract Purpose In children with Autism Spectrum Disorder (ASD), motor disorders (MD) are a common occurrence, and developing effective interventions continues to be challenging. This study aims to investigate the effects of a 12-week ball combination training program (BCTP) combined with continuous theta burst stimulation (cTBS) on MD in children with ASD. Methods: The study employed a 4 (cTBS, BCTP, cTBS*BCTP, control group) × 2 (pre-test, post-test) mixed design methodology. 50 participants were allocated to three experimental groups(38) and one control group(12), receiving interventions for a period of 12 weeks. MD were measured using the Movement Assessment Battery for Children - Second Edition (MABC-2). Results: Results indicated that the cTBS*BCTP group significantly improved the overall MABC-2 scores (P < 0.05) and Manual dexterity scores (P < 0.05) in children with ASD, and the BCTP group also significantly improved overall MABC-2 scores. Compared to the control group, the effect size for the cTBS*BCTP group was 1.03 (95% CI: 0.13 to 1.94), showing the best intervention effect, outperforming the BCTP group (effect size: 0.82, 95% CI: -0.09 to 1.72) and the cTBS group (effect size: 0.43, 95% CI: -0.38 to 1.23). Conclusion: Overall, the BCTP*cTBS group showed the most significant intervention effects across various dimensions, demonstrating the efficacy of combined interventions in improving MD in children with ASD, confirming that combined interventions are superior to single interventions.